Change in D3Cr muscle mass in oldest old men and its association with changes in grip strength and walking speed - Megan Hetherington-Rauth; Chuck E. McCulloch; William J. Evans; Marc Hellerstein; Mahalakshmi Shankaran; Jane A. Cauley; Kris Ensrud; Lisa Langsetmo; Eric S. Orwoll; Peggy M. Cawthon (PLoS ONE, 2025)
Background The use of lean soft tissue (LST) mass as a surrogate measurement of skeletal muscle mass (SMM) has led to the conclusion that muscle loss is poorly related to functional decline. We hypothesized that when using a more accurate measure of SMM determined by D3-creatine dilution (D3Cr), longitudinal changes in SMM will be similar in magnitude to changes in strength and physical performance and that skeletal muscle mass will partially mediate the relationship of age with these outcomes. Methods We measured change in D3Cr muscle mass (kg), handgrip strength (kg), and 6m walk speed (m/s) in 208 men from the Osteoporotic Fractures in Men Study (85.2 ± 4.3 years) over an average of 6.1 years follow-up. Mixed linear effects models adjusted for potential confounders were used to examine the relationship of changes in D3Cr muscle mass with changes in grip strength and walking speed. Results Annual losses of D3Cr muscle mass, grip strength, and walking speed were 2.1%, 2.2%, and 2.6%, respectively (p < 0.001). Each additional kg loss in D3Cr muscle mass was associated with a 0.55 kg loss in grip strength and a 0.01 m/s loss in walking speed independent of changes in age (p < 0.001). 41.3% and 22.4% of the relationship between age and loss of grip strength and walking speed, respectively, was attributed to loss of D3Cr muscle mass (p < 0.001). Conclusion Skeletal muscle mass may have a more important role than previously considered and should not be overlooked as a potentially modifiable determinant in the loss of strength and performance in older age.